Role of Copper and Zinc Ions in the Hydrolytic Degradation of Neurodegeneration-Related Peptides - Valentina Pirota; Enrico Monzani; Simone Dell’Acqua; Chiara Bacchella (Molecules)
Spontaneous cleavage reactions normally occur in vivo on amino acid peptide backbones, leading to fragmentation products that can have different physiological roles and toxicity, particularly when the substrate of the hydrolytic processes are neuronal peptides and proteins highly related to neurodegeneration. We report a hydrolytic study performed with the HPLC-MS technique at different temperatures (4 °C and 37 °C) on peptide fragments of different neuronal proteins (amyloid-β, tau, and α-synuclein) in physiological conditions in the presence of Cu2+ and Zn2+ ions, two metal ions found at millimolar concentrations in amyloid plaques. The coordination of these metal ions with these peptides significantly protects their backbones toward hydrolytic degradation, preserving the entire sequences over two weeks in solution, while the free peptides in the same buffer are fully fragmented after the same or even shorter incubation period. Our data show that peptide cleavage is not only ruled by the chemical sensitivity of amino acids, but the peptide conformation changes induced by metal coordination influence hydrolytic reactions. The enhanced stability of neuronal peptides provided by metal coordination can increase local levels of amyloidogenic species capable of seeding fibril growth, resulting in aberrant protein depositions and deficits in neuronal activity.